Comparative Study of Efficacy of Letrozole with Clomiphene Citrate in Anovulatory Women with Polycystic Ovarian Syndrome (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Polycystic Ovary Syndrome (PCOS) is one of the most common endocrine disorders among women of reproductive age and a major cause of anovulatory infertility. Ovulation induction remains the cornerstone of treatment for infertile women with PCOS. Among the available pharmacological agents, Letrozole and Clomiphene Citrate are widely used, with recent evidence suggesting superior reproductive outcomes with Letrozole.Aim & Objective: To compare the efficacy and safety of Letrozole and Clomiphene Citrate for ovulation induction in women with PCOS.Materials & Methods: This comparative study was conducted at Gandhi Hospital between July 2022 and September 2023 and included 100 women diagnosed with PCOS. Participants were randomly allocated into two equal groups. The Letrozole group received 2.5 mg twice daily, while the Clomiphene Citrate group received 100 mg daily for five days starting from day 3 of the menstrual cycle. Follicular development was monitored by ultrasonography, and endometrial thickness, hormonal profile, number of mature follicles, and duration of stimulation were assessed.Results: Letrozole showed significantly better outcomes than Clomiphene Citrate. Women treated with Letrozole demonstrated a higher number of mature follicles (>14 mm and >18 mm), greater endometrial thickness, and more favorable hormonal profiles. Although the Clomiphene Citrate group developed a higher total number of follicles, follicular quality and endometrial receptivity were superior in the Letrozole group. Furthermore, Letrozole required a shorter duration of stimulation, indicating improved treatment efficiency.Conclusion: Letrozole is more effective than Clomiphene Citrate for ovulation induction in women with PCOS, providing better follicular maturation, enhanced endometrial receptivity, and improved hormonal response. These findings support Letrozole as a preferred first-line therapy for managing anovulatory infertility associated with PCOS.